O Uso de softwares educativos nas aulas de genética do ensino médio - Germano, Thiago da Costa (2019)
Due to several factors such as traditional classes, difficulty in accessing some didactic materials (use of resources in laboratories, for example) and lag in the teaching of basic mathematics, the teaching of genetics becomes a challenge for a portion of students enrolled in teaching. Brazilian midfielder. Thus, this research aims to verify the occurrence of benefits in learning the Mendelian genetics content addressed in the curriculum of a state high school, located in the city of Cascavel / CE, by the application of Educational Software (SE) available by authors of biology textbooks. This study is based on bibliographic research, such as books, scientific articles, theses and dissertations, as well as magazines. In addition, qualitative, quantitative and descriptive analyzes of the interviews with the actors of the latter are performed. They are the Biology teacher and the randomly selected students. During one academic quarter, ten students from the 3rd grade participated in the research, where five were in the classes offered by the teacher and five in the school's Computer Laboratory (LEI) with the researcher to use ES with the content. identical to classroom work and synchronously. The group that underwent the use of ES in the LEI was called Test or Experimental Group and those who were with the teacher, Control Group. Through the tests (pre and post-test) it was possible to realize that the ES have relevance in learning Mendelian genetics addressed in high school, as well as in facilitating the teaching activities that seek to transcend the traditionalist view in the classroom seeking active learners in schools. its own educational process. Realizing the importance of ES in the teaching of genetics, an Educational Product was elaborated called “Didactic Proposals for the teaching of Mendelian genetics using Educational Software” for teaching professionals working in the Biology discipline. This document aims to mediate the pedagogical situations through the application of the ES and, thus, improve their teaching methodologies and make their classes attractive and dynamic.